Hybrid automata system for emotion embodiment in upper extremity rehabilitation system - Sidek, Shahrul Na'im; Ghazali, Aimi Shazwani; Wok, Saodah (International Institute of Applied Informatics, 2015)
This paper highlights the embodiment of emotions which is structured using hybrid automata framework. Each initialization value, modes, condition for each mode, guard conditions, and transition between modes of the automata model designed for robot-assisted rehabilitation system are elaborated. A structured experimental setup was designed to invoke the emotion of the subject and to test the integration between detected emotion with the rehabilitation platform. The evaluation of the hybrid automata proposed is based on real time application. The result demonstrates the efficacy of hybrid automata approach in the rehabilitation application where emotion of the subject is taken into consideration in deploying suitable upper extremity rehabilitation tasks for Human Machine Interaction (HMI) applications.